Contando aprendizajes artísticos: una comprensión desde lo socio-emocional (2022)
This degree project shows the categories, the subcategories and the characteristics identified in the comprehension of the relations created between artistic learning and socioemotional education; result of the systematization of the remote pedagogical practice carried out with girls from 7 to 15 years old, at the Santa Maria Foundation (SMF) since 2020-2 until 2021-2. The experience systematization methodology of Oscar Jara (1994) is used to know the author’s interest, which leads to delimit the central approaches of this qualitative research. The sources of the information collected are the process logs; the semi-structured interviews applied to students, about the perception of the artistic learning process and the graphic representations, elaborated by them. The collected information is organized and classified on a grid, which the different categories, subcategories and characteristics are known through the triangulation process; thus the critical interpretation of the study outcomes. With the created learning, the reflective written memory is presented for the contribution of didactic scope; aimed at colleagues who develop their remote pedagogical practice at SMF, generally, educators who work with children and adolescences from 7 to 15 years old, interested in the field of artistic education, connected with socio-emotional education as a learning construct axis.